PENGARUH GANITRI (ELOEOCARPUS GANITRUS) TERHADAP PERCEPATAN REHABILITASI OTOT PASIEN POST STROKE DI RUMAH SAKIT GATOEL MOJOKERTO - Marasabessy, Jufri; SUDIYANTO, Henry (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2019)
The key to successful post-stroke rehabilitation is the duration and intensity of physical therapy exercises. The success can be increased by adding complementary therapies to the rehabilitation process. The purpose of this study was to investigate the effect of ganitri (Eloeocarpus Ganitrus) on the acceleration of post-stroke muscle rehabilitation in the Gatoel Hospital of Mojokerto.In this study the type of research used is experimental research While the research design used is Quasy-Experiment.Teknik sampling used is Purposive Sampling with the number of samples in each group is 14 respondents. Measuring tool used is MMT (Manual Mscle Testing), intervention given is in the form of use of bracelets and necklace ganitri for 5 weeks. Data were analyzed by Wilcoxon Signed Ranks TestThe result of pre-test and post-test result showed that post stroke patient's muscle strength in the control group was half pre test (50%), while in post test (58%). The result of statistical test shows indigo P = 0,083 (P> 0,05). While in the treatment group most of the pre test (60%), while the post test half (50%). The result of statistical test shows that P = 0,001 (P <0,05), meaning that there is ganitri effect (Eleoecarpus Ganitrus) to acceleration of muscle rehabilitation process of post stroke patient.Electromagnetic power of 10,000 gauss in Faraday equilibrium, the result of alkaline electron conduction. Thus ganitri expected to be a complementary alternative therapy in the form of the use of bracelets and necklaces so that the success of increased muscle strength post stroke patients can be achieved with the maximum.Keywords: Rehabilitation, Ganitri (Eleoecarpus Ganitrus), Muscle Power